2017
DOI: 10.1371/journal.pgen.1006731
|View full text |Cite
|
Sign up to set email alerts
|

Natural variation of piRNA expression affects immunity to transposable elements

Abstract: In the Drosophila germline, transposable elements (TEs) are silenced by PIWI-interacting RNA (piRNA) that originate from distinct genomic regions termed piRNA clusters and are processed by PIWI-subfamily Argonaute proteins. Here, we explore the variation in the ability to restrain an alien TE in different Drosophila strains. The I-element is a retrotransposon involved in the phenomenon of I-R hybrid dysgenesis in Drosophila melanogaster. Genomes of R strains do not contain active I-elements, but harbour remnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 71 publications
(145 reference statements)
2
24
0
Order By: Relevance
“…localization and transposition machinery may simplify their regulation by the genome. We observed expansions of all HeT-A subfamilies and TAHRE, but not the TART elements in the longest telomere strain, which is consistent with HeT-A being more sensitive to piRNA repression than TART as suggested by [70]. Similarly, we found that TART elements are segregated from HeT-A family elements and TAHRE in the telomere.…”
Section: Is Telomere Restriction Domestication or An Evolutionary Strsupporting
confidence: 87%
“…localization and transposition machinery may simplify their regulation by the genome. We observed expansions of all HeT-A subfamilies and TAHRE, but not the TART elements in the longest telomere strain, which is consistent with HeT-A being more sensitive to piRNA repression than TART as suggested by [70]. Similarly, we found that TART elements are segregated from HeT-A family elements and TAHRE in the telomere.…”
Section: Is Telomere Restriction Domestication or An Evolutionary Strsupporting
confidence: 87%
“…The R strain w K , which was used for the I-TG transgenesis, is a strong reactive strain, meaning that a very high level of I-element transposition was observed when introducing functional I-elements by a cross between w K females and inducer males. In w K ovaries, only a minimal amount of ancestral I-derived piRNAs is produced [19,24,40] (Tables S3 and S4). One could argue that initially, the chromatin structure and piRNA production from the I-transgenes in all strains were the same, although later, in the course of the strain-specific history, the transgenes in the 2.1 s and 2.4 s strains became stronger, which resulted in higher Rhi occupancy and more efficient piRNA production.…”
Section: Transgenic Pirna Cluster Establishment Is Independent Of Higmentioning
confidence: 99%
“…We found that the increase in the level of piRNAs targeting I-TG transgenes does not stimulate additional changes of the chromatin state or piRNA production by the transgenes. The study of paternal transgene inheritance by crossing transgenic males with w K females whose oocyte cytoplasm is the poorest in I-specific piRNAs [24] suggests that heterochromatinization and piRNA production at the target locus are activated by a minimum threshold level of complementary piRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the telomeres need to produce both the intact TE mRNA required for telomere elongation, as well as piRNAs that target these TE mRNA in order to regulate optimal telomere length. Indeed, altering this balance can lead to disruption of telomere length control (3,33).…”
Section: Introductionmentioning
confidence: 99%